2005
DOI: 10.1111/j.1468-1331.2005.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term safety and tolerability of high‐dose interferon β‐1a in relapsing–remitting multiple sclerosis: 4‐year data from the PRISMS study

Abstract: In the prevention of relapses and disability by interferon subcutaneously in multiple sclerosis (PRISMS) study, 560 patients with relapsing-remitting multiple sclerosis were randomized to receive subcutaneous interferon (IFN) beta-1a, 22 or 44 mug three times weekly, or placebo, for 2 years. Patients receiving placebo were then re-randomized to one of the two doses of IFN beta-1a for a further 2 years, whilst patients receiving active treatment continued their original treatment. Safety assessments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 11 publications
2
55
1
4
Order By: Relevance
“…189,208 As noted in the original trial report, 189 patients receiving the 44-µg dose were less likely to have a sustained worsening in ambulation than those receiving placebo (7% vs. 13%; p < 0.05); however, the corresponding value for those receiving the 22-µg dose (12%) was not significantly different from that for placebo. Subsequently, Gold et al 231 reported that, although patients in all three groups increased their scores from baseline on the Center for Epidemiologic Studies Depression Rating Scale, these changes were not significantly different between the groups (44 µg: 0.2, 22 µg: 1.8, placebo: 0.9; p = 0.60). Similarly, the risk of exceeding the cut-off score for depression on this scale was not significantly different between either the 44-µg arm (RR 0.7, 95% CI 0.3 to 1.6) or the 22-µg arm (RR 0.8, 95% CI 0.3 to 1.8) and the placebo arm and the proportions of patients exceeding the cut-off on the Beck Hopelessness Scale were not significantly different between the placebo arm (6.9%) and either the 44-µg arm (6.9%; p = 1.0) or the 22-µg arm (10.5%; p = 0.55).…”
Section: Multiple Sclerosis Symptoms and Health-related Quality Of Lifementioning
confidence: 96%
See 1 more Smart Citation
“…189,208 As noted in the original trial report, 189 patients receiving the 44-µg dose were less likely to have a sustained worsening in ambulation than those receiving placebo (7% vs. 13%; p < 0.05); however, the corresponding value for those receiving the 22-µg dose (12%) was not significantly different from that for placebo. Subsequently, Gold et al 231 reported that, although patients in all three groups increased their scores from baseline on the Center for Epidemiologic Studies Depression Rating Scale, these changes were not significantly different between the groups (44 µg: 0.2, 22 µg: 1.8, placebo: 0.9; p = 0.60). Similarly, the risk of exceeding the cut-off score for depression on this scale was not significantly different between either the 44-µg arm (RR 0.7, 95% CI 0.3 to 1.6) or the 22-µg arm (RR 0.8, 95% CI 0.3 to 1.8) and the placebo arm and the proportions of patients exceeding the cut-off on the Beck Hopelessness Scale were not significantly different between the placebo arm (6.9%) and either the 44-µg arm (6.9%; p = 1.0) or the 22-µg arm (10.5%; p = 0.55).…”
Section: Multiple Sclerosis Symptoms and Health-related Quality Of Lifementioning
confidence: 96%
“…170,226,[229][230][231] Of these 27 trials, one evaluated HRQoL measures alone 181 and one evaluated AEs alone. 182 In addition, two trials reported on mixed populations.…”
Section: Summary: Clinically Isolated Syndromementioning
confidence: 99%
“…27 This statement is not supported by the present results, which are consistent with reported results from a 4-year study of SC IFNβ-1a in which the percentage of people reporting ISRs did not change over the 4-year study period. 31 Recently, Treadaway et al 14 reported that 12% of patients with MS receiving a DMT were nonadherent (having missed more than one injection in the previous 4 weeks) because of concerns about ISRs and pain. Using a similar definition of adherence, the results of the present study were similar, with 11% of patients reporting having missed one or more injections because of ISRs.…”
Section: Resultsmentioning
confidence: 99%
“…4 The occurrence of individual ISR symptoms varied, with 64% of patients treated with glatiramer acetate experiencing pain, 57% erythema, 27% inflammation, and 19% induration. 4 Inflammation was the most common ISR reported with IFNβ-1a SC TIW therapy, 5 whereas pain and erythema were the most common ISR symptoms associated with glatiramer acetate. 4,6,7 Infection and skin necrosis are more serious ISRs that occur much less frequently but may require treatment with antibiotics and, in rare cases, surgical intervention.…”
Section: Disease-modifying Therapies Ifnβ β and Glatiramer Acetatementioning
confidence: 99%
“…2,5,9,[30][31][32][33] The occurrence of FLSs after IFNβ-1b treatment may be influenced by factors such as body size and age. Sixty percent of patients 18-28 years of age experienced FLSs, compared to 37% of patients 42-50 years of age, during the early course of treatment with IFNβ-1b.…”
Section: Disease-modifying Therapies Ifnβ β and Glatiramer Acetatementioning
confidence: 99%